EFEKTIVITAS PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN REMAJA TENTANG PELECEHAN SEKSUAL DI SMK 1 PIRI YOGYAKARTA - Melina, Fitria; Shelamita, Shelamita (Jurnal Kesehatan Samodra Ilmu (JKSI), 2023)
Background: CATAHU recorded cases of sexual harassment against women received by various community organizations and government institutions spread across all provinces in Indonesia as well as direct complaints received by Komnas Perempuan for cases of violence in 2022 in Indonesia totaling 299,911 cases. The highest cases of sexual violence were from Sleman Regency reaching 44%, followed by Yogyakarta City 27%, Bantul reaching 13%, Kulon Progo and Gunung Kidul 2% and outside DIY 12% with the perpetrators being on average the people closest to the victim. Research methods: This research is a quantitative research using the Pre-Experimental Research Method with the One-Group Pretest-Posttes Design. The population in this study was 218 people. The sampling technique is accidental sampling. The sample size obtained was 30 respondents. The instrument in this study was a questionnaire. Methods of data analysis using univariate Results and discussion: Most of the frequency distribution of knowledge of sexual harassment before being given health education with audio-visual media was sufficient (63.3%), knowledge of sexual harassment after being given health education was mostly good (70.0%). The results of the Wilcoxon Penkes Test with Audio Visual Media are Effective for Increasing Adolescents' Knowledge of Sexual Harassment at Piri1 Yogyakarta Vocational High School, because the significant value is 0.000 <0.05. The Effectiveness of Health Education with Audio Visual Media about Sexual Harassment Against Adolescent Knowledge at SMK Piri 1 Yogyakarta